Chromogranin-A production and fragmentation in patients with Takayasu arteritis. Issue 1 (December 2016) - Tombetti, Enrico; Colombo, Barbara; Di Chio, Maria; Sartorelli, Silvia; Papa, Maurizio; Salerno, Annalaura; Bozzolo, Enrica; Tombolini, Elisabetta; Benedetti, Giulia; Godi, Claudia; Lanzani, Chiara; Rovere-Querini, Patrizia; et al.
Abstract Background Chromogranin-A (CgA) is a secretory protein processed into peptides that regulate angiogenesis and vascular cells activation, migration and proliferation. These processes may influence arterial inflammation and remodelling in Takayasu arteritis (TA). Methods Plasma levels of full-length CgA (CgA439 ), CgA fragments lacking the C-terminal region (CgA-FRs) and the N-terminal fragment, CgA1–76 (vasostatin-1, VS-1) were analysed in 42 patients with TA and 20 healthy age-matched controls. Vascular remodelling was longitudinally assessed by imaging. CgA peptides were related to markers of systemic and local inflammation, disease activity and vascular remodelling. Results Levels of CgA-FRs and VS-1 were increased in TA. Treatment with proton-pump inhibitors (PPIs) and arterial hypertension partially accounted for CgA levels and high inter-patient variability. CgA439, CgA-FRs and VS-1 levels did not reflect disease activity or extent. Markers of systemic or local inflammation correlated with higher CgA-FRs and VS-1 in normotensive patients and with higher CgA439 in hypertensive patients. Treatment with non-biologic anti-rheumatic agents was associated with increased CgA-FRs and a distinctive regulation of CgA processing. Reduced blood levels of anti-angiogenic CgA peptides were associated with vascular remodelling in the groups of patients on PPIs and with arterial hypertension. Conclusions The plasma levels of CgA fragments are markedly increased in TA as a consequence of disease- and therapy-related variables. Anti-angiogenic forms of CgA may limit vascular remodelling. Given the effect of the various CgA peptides, it is advisable to limit the therapeutic prescriptions that might influence CgA-derived peptide levels to clearly agreed medical indications until further data become available.